Clinical profile of young adult diabetic patients attending hospital OPD of a tertiary care centre in central India - P Soni; A Zoheb (International Journal of Medical Research and Review, 2015)
Background: Most diabetes prevention efforts in Indian communities have been secondary or tertiary prevention programs targeting adults with type 2 diabetes. The approaches often combine a number of strategies, including health education, health fairs, fitness programs, nutrition education, etc., and are delivered in a shotgun method with the expectation that one or two of the strategies will be effective.Material and methods: A Hospital-based cross-sectional study was carried out in the Department of Medicine of Chirayu Medical College and Hospital, Bhopal located in central India. All the young adult patients aged between 20-40 years were included in the study and questionnaire was used to record the clinical profile of the patients.Results: Diabetes Mellitus was found more in the age group of 35-40 years followed by 30-35 years age group. 08% of the cases had positive family history of diabetes mellitus and mean BMI of the cases was 23.2 kg/m2. Out of total 76 symptomatic patients, complications of diabetes mellitus were found in 32(42.1%) of the cases. Most common complication found was genital infections seen in 18(13.2%).Conclusion: Early sign and symptoms of diabetes should be explained in the community through educational activities, so that the community level of understanding and knowledge about the disease increased and at the same time patients should be reinforced to use the health care services for proper control of sign and symptoms and complications of diabetes and to modify the lifestyle of the population diagnosed with diabetes mellitus.